To Quote or Not to Quote? Categorizing Quotations in the Epistle to the Hebrews. (March 2022) - Cooper, Mark
An overview of the appendices in NA 28 and UBS 5 reveals that the editors agreed regarding the number of quotations in Hebrews on 37 occasions. They disagreed, however, as to whether an intertext was a quotation or an allusion on nine occasions. The compilers of these lists did not provide a basis for their conclusions, and inability to agree on the number of intertexts could be due to multiple reasons. The purpose of this study, therefore, was to develop a set of criteria by which to identify quotations in Hebrews. Auctor's quotations were determined to possess four characteristics: (1) introductory formula, (2) a recognizable source, (3) verbal correspondence with the hypotext and (4) syntactical tension. These four characteristics were then utilized to assess the nine disputed intertexts between NA 28 and UBS 5 . By assessing the nine intertexts for the presence of the criteria, four out of the nine were determined to be quotations, whereas five were deemed to be allusions.